Dehydrogenation of propane over PtSn/SBA-15 catalysts: effect of the amount of metal loading and state. Issue 36 (23rd April 2015) - Fan, Xiaoqiang; Li, Jianmei; Zhao, Zhen; Wei, Yuechang; Liu, Jian; Duan, Aijun; Jiang, Guiyuan
<x xml:space="preserve">Abstract</x> The state and distribution of Pt and Sn change with different metal amounts, resulting in different catalytic performances on PtSn/SBA-15.